Case Report: A Case of Sintilimab-Induced Cystitis/Ureteritis and Review of Sintilimab-Related Adverse Events - Tu, Lingfang; Ye, Yuan; Tang, Xiaoping; Liang, Zhen; You, Qihan; Zhou, Jianying; Pan, Zhijie (Frontiers in Oncology, 2021)
Immune checkpoint inhibitors (ICIs) have been proven to be beneficial in multiple advanced malignancies. However, the widespread use of ICIs also occurred with various immune-related adverse events (irAEs). Here, we first report a case of sintilimab-related cystitis/ureteritis. A 53-year-old man with driver gene-negative pulmonary adenocarcinoma (cT1cN3M1c, Stage IVB) was being treated with sintilimab in combination of paclitaxel-albumin and bevacizumab as second-line treatment. He was hospitalized for haematuria, pollakiuria, painful micturition and low back pain after three courses. Urinalysis showed red blood cells (RBCs) and white blood cells (WBCs) were obviously increased, and serum creatinine (sCr) level was also significantly elevated. Urine culture and cytology were both negative, and cystoscopy revealed diffused redness of bladder mucosa. Urinary ultrasonography showed mild hydronephrosis and dilated ureter. The patient was diagnosed as immunotherapy-related cystitis/ureteritis after a multidisciplinary team (MDT) meeting. Once the diagnosis was made, corticosteroid therapy was given, which rapidly resolved the patient’s symptoms and signs. Computer tomography angiography (CTA) and CT urography (CTU) was conducted after sCr level was back to normal and demonstrated ureter dilation and hydroureter. Once symptoms relieved, bladder biopsy was performed and confirmed the bladder inflammation. The patient was subsequently switched to maintenance dose of methylprednisolone and tapered gradually. Since sintilimab has been used in advanced malignancies, we first reported a rare case of sintilimab-induced cystitis/ureteritis and summarized sintilimab-related adverse events to improve the assessment and management of irAEs.